Leading a Digital Transformation in Pharmacy Education with a Pandemic as the Accelerant - Edith Mirzaian; Kari L. Franson (Pharmacy, 2021)
The global COVID-19 pandemic has not only posed a challenge to education but created an opportunity to spearhead a digital transformation and the novel delivery of a Pharm.D. curriculum. The process to transform the curriculum in a sustainable and iterative manner involved multiple steps including: (1) Communication, (2) Maintaining faculty engagement, (3) Allowing outside the box thinking, (4) Providing resources and tools and (5) Creating accountability and timelines. At our institution, we have been interested in digital transformation since completing our interview of global leaders. We began our journey using the current COVID-19 pandemic as an accelerant for change. Digital transformation in any industry is not a simple undertaking. However, with planning, aligned organizational interests, consistent and regular communication, provision of resources and tools, engaging faculty and creating accountability and timelines with deliverables the implementation can be successful. When the global pandemic wanes and educational institutions commence in-person classes, having undergone the stages of digital transformation, we will be able to embrace these changes and transform education, not having to reproduce pre-pandemic educational systems.